Immune-Related miRNA-195-5p Inhibits the Progression of Lung Adenocarcinoma by Targeting Polypyrimidine Tract-Binding Protein 1 - Duan, Lincan; Wang, Juan; Zhang, Dahang; Yuan, Yixiao; Tang, Lin; Zhou, Yongchun; Jiang, Xiulin (Frontiers in Oncology, 2022)
Abstract Purpose: Lung cancer is the most common type of cancer and leading cause of cancer-related death worldwide, resulting in huge economic and social burden. MiRNA-195-5p plays crucial roles in the initiation and progression of cancer. However, the significance of the miRNA-195-5p/polypyrimidine tract-binding protein 1 (miRNA-195-5p/PTBP1) axis in the progression of lung adenocarcinoma (LUAD) remains unclear. Methods: Data were collected from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. The starBase database was employed to examine the expression of miRNA-195-5p, while the Kaplan–Meier plotter, UALCAN, and Gene Expression Profiling Interactive Analysis (GEPIA) databases were utilized to analyze the tumor stage and prognostic value of miRNA and PTBP1. GeneMANIA and Search Tool for the Retrieval of Interacting Genes (STRING) were used to perform Gene Ontology/Kyoto Encyclopedia of Genes and Genomes (GO/KEGG) functional enrichment and protein–protein interaction analysis for PTBP1 co-expression. Quantitative reverse transcription-polymerase chain reaction assay was conducted to detect the expression levels of miRNA-195-5p in LUAD cell lines and tissues. The effects of miRNA-195-5p on cell proliferation and migration were examined using the cell growth curve, clone information, transwell assays, and wound healing assays. Results: The expression of miRNA-195-5p was down-regulated in LUAD cancer and cell lines. Importantly, its low levels were correlated with the tumor stage, lymph node metastasis, and poor prognosis in LUAD. Overexpression of miR-195-5p significantly inhibited cell growth and migration, promotes cell apoptosis. Further study revealed that PTBP1 is a target gene of miRNA-195-5p, and overexpression of miRNA-195-5p inhibited the progression of LUAD by inhibiting PTBP1 expression. MiRNA-195-5p expression was correlated with immune infiltration in lung adenocarcinoma. Moreover, PTBP1 was negatively correlated with diverse immune cell infiltration and drug sensitivity. Conclusion: Our findings uncover a pivotal mechanism that miRNA-195-5p by modulate PTBP1 expression to inhibition the progression of LUAD. MiRNA-195-5p could be a novel diagnostic and prognostic molecular marker for LUAD.